High Resolution Soft X-ray Spectroscopy and the Quest for the Hot (5–10 MK) Plasma in Solar Active Regions - Del Zanna, Giulio; Andretta, Vincenzo; Cargill, Peter J.; Corso, Alain J.; Daw, Adrian N.; Golub, Leon; Klimchuk, James A.; Mason, Helen E. (Frontiers in Astronomy and Space Sciences, 2021)
We discuss the diagnostics available to study the 5--10 MK plasma in the solar corona, which is key to understanding the heating in the cores of solar active regions. We present several simulated spectra, and show that excellent diagnostics are available in the soft X-rays, around 100 Angstroms, as six ionisation stages of Fe can simultaneously be observed, and electron densities derived, within a narrow spectral region. As this spectral range is almost unexplored, we present an analysis of available and simulated spectra, to compare the hot emission with the cooler component. We adopt recently designed multilayers to present estimates of count rates in the hot lines, with a baseline spectrometer design. Excellent count rates are found, opening up the exciting opportunity to obtain high-resolution spectroscopy of hot plasma.